Dairy efficiency and technological properties of red-and-white cows of povolzh'e type - A. P. Velmatov; A. M. Guryanov; M. N. Malkin; T. N. Tishkina; A. A. Velmatov (Аграрная наука Евро-Северо-Востока, 2016)
The purpose of research is to study milk production and technological properties of red-and-white cows which have been bred within its own genotype. Two groups of heifers with 18 animals in each were selected for the experiment. The structure of the first group consisted of the second-generation hybrids (1/4 RW + 3/4 RWH). The second group consisted of hybrids of the second generation (1/4 RW +3/4 RWH) obtained from bred within its own genotype. Crossbred animals breded within its own genotype yielded 6263 kg of milk for the first lactation which is 456 kg higher compared with the same age cows breded ordinary. Significant differences between the groups have been identified by the output of milk fat - 23.8 kg (P < 0.001) and by milk protein - 17.4 kg (P < 0.01). According to the exterior linear estimation sufficiently aligned results with low variability are marked. So animals belong to dairy body type and with good feeding and keeping can be used in selection for more efficient use of breed capacity in desirable direction, i.e. in the direction of pelvis width increasing and strong constitution. The data indicate that the cows generally have cup-shaped (54.2…66.6%) and bath-shaped (23.3…38.8%) udders. Cow's udder is firmly attached to the body, with conspicuous mammary veins, covered with a thin elastic skin. Cows practically does not have udder lobulation, udder bottom is mainly horizontal. According to the intensity of milk flow group differences amounted to 0.2 kg / min (P < 0.01) in favor of the animals breded within its own breed. Therefore, both groups of animals are characterized by good morphological and functional properties of the udder and are ideally suited to the currently applied milking technology.